Management of Vulvovaginal Candidiasis in Pregnancy - Levina, Jessica; Ocviyanti, Dwiana; Adawiyah, Robiatul (Indonesian Journal of Obstetrics and Gynecology, 2024)
Pregnancy is a risk factor for vulvovaginal candidiasis (VVC). The most common cause of VVC in pregnancy is Candida albicans. During pregnancy, physiological changes occur, such as increased levels of estrogen, lower vaginal pH, increased production of vaginal mucosal glycogen and immunological changes so that Candida colonization in the vagina increases. Increased colonization can be symptomatic or asymptomatic. When symptoms and signs of vulvar pruritus, pain, swelling, redness, burning, dyspareunia, dysuria, vulvar edema, fissures, excoriation and vaginal discharge are found, it is necessary to perform microscopic examination and/or fungal culture to establish the diagnosis of VVC. Topical intravaginal antifungal therapy such as clotrimazole and nystatin, are the recommended treatment for VVC in pregnancy that has been shown its safety. Treatment with oral antifungal is not recommended because of the risk of causing congenital abnormalities in the fetus. Prophylactic administration in the last trimester of pregnancy in asymptomatic VVC cases provides good pregnancy and neonatal outcomes but is still being debated. In severe, prolonged or recurrent cases of VVC, other co-infections may be sought which may also need to be managed. Administration of probiotics for VVC therapy still requires further research.